Effect of dry fodder based complete feed on carcass composition and serum profile of Madras Red sheep: Effect of dry fodder based complete feed on carcass composition and serum profile of Madras Red sheep - Vasan, P; Sivakumar, T (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was carried out to investigate the effect of complete feed regimen on the carcass composition and serum profile of Madras Red sheep. Sixteen numbers of Madras Red lambs (90 d old) were dewormed and maintained on a dry fodder based complete feed regimen (14.25 % crude protein and 61.07 % TDN) for a period of 180 days. The animals were provided with ad libitum water and feed at all times. During third month of trial, blood samples were collected from individual animals via jugular vein for serum mineral and enzyme profile. At the end of 270 d the animals were slaughtered and the carcass parameters recorded. The average final body weight was 18.03 ± 0.89 kg and the mean daily body weight gain was 57.58 ± 4.65 g/day. The dry matter intake was 0.93 ± 0.08 kg/day. the carcass traits including those of edible and non edible portions and serum profile of Madras Red sheep maintained under intensive management system fed dry fodder based complete feed were found to be superior to those of Nellore and Garole sheep breeds..